La transdisciplinariedad y la complementariedad paradigmática, dos eslabones para la investigación científica y el desarrollo educativo universitario (Tema Central) - Vásquez, Miguel (2018)
Transcomplexity is an epistemological perspective that seeks to integrate the postulates of the theory of complex thought and transdisciplinarity -which is inserted in the meta-domains of knowledge-, in which several social sciences converge. From here comes the construction of university knowledge between the ontological being and the object in the phenomenal world, with a paradigmatic complementarity of which they are part and which allows them a multidimensional epistemic vision. Therefore, the way to conduct research and knowledge under this meaning necessarily requires rethinking, in the methodological practice, the discussion processes that facilitate higher education from a prospectivist point of view, with respect to the phenomenal reality of the Latin American university, that allow to create collaborative integration strategies from science, technology and society (CTS).